Pertimbangan Hakim dalam Menentukan Kematian Korban dalam Tindak Pidana Pembunuhan (Studi Kasus Putusan Nomor: 26/Pid.B/2014/Pn.Atb) - Affiani, Rifrinda Nur; Suyatna (Indonesian Journal of Law and Justice, 2024)
People who commit legal errors and cause the consequences of these legal actions must be able to take responsibility for the consequences of their actions. Murder is the act of taking another person's life intentionally and the aim is to take someone's life, while the crime of assault is a crime whose target is the human body. The aim of this research is to find out how the judge views the death of the victim in the crime of murder. This research uses normative juridical methods, meaning library research that uses library legal material sources using a legal approach and a case approach. In this case the researcher does not agree with the judge's decision because according to the researcher what is meant by the crime of murder is the victim who should have died when the incident occurred, but at that time the victim also died. did not die immediately, therefore the appropriate charge is for committing a criminal act of serious abuse which resulted in death. The results of the research discussion can be concluded that the judge's consideration in handing down and determining the death of the victim was incorrect.